Quantitative comparison of the efficacy of various compounds in lowering intracellular cholesterol levels in Niemann-Pick type C fibroblasts. - Zachary T Wehrmann; Tyler W Hulett; Kara L Huegel; Kevin T Vaughan; Olaf Wiest; Paul Helquist; Holly Goodson (PLoS ONE, 2012)
Niemann-Pick Type C disease (NPC) is a lethal, autosomal recessive disorder caused by mutations in the NPC1 and NPC2 cholesterol transport proteins. NPC's hallmark symptoms include an accumulation of unesterified cholesterol and other lipids in the late endosomal and lysosomal cellular compartments, causing progressive neurodegeneration and death. Although the age of onset may vary in those affected, NPC most often manifests in juveniles, and is usually fatal before adolescence. In this study, we investigated the effects of various drugs, many of which modify the epigenetic control of NPC1/NPC2 gene expression, in lowering the otherwise harmful elevated intracellular cholesterol levels in NPC cells. Our studies utilized a previously described image analysis technique, which allowed us to make quantitative comparisons of the efficacy of these drugs in lowering cholesterol levels in a common NPC1 mutant model. Of the drugs analyzed, several that have been previously studied (vorinostat, panobinostat, and β-cyclodextrin) significantly lowered the relative amount of unesterified cellular cholesterol, consistent with earlier observations. In addition, a novel potential treatment, rapamycin, likewise alleviated the NPC phenotype. We also studied combinations of effective compounds with β-cyclodextrin; the addition of β-cyclodextrin significantly enhanced the cholesterol-lowering activity of vorinostat and panobinostat, but had mixed effects with rapamycin. Collectively, these results may provide a basis for the eventual development of improved NPC therapies.